(untitled) (Tạp chí Y học Cộng đồng, 2026)
Objective: To evaluate the treatment outcomes of acute appendicitis using laparoscopic surgery at Vinh Tuong District Medical Center. Methods: A descriptive cross-sectional study was conducted on 66 patients diagnosed with acute appendicitis and treated with laparoscopic surgery. Data on epidemiological characteristics, clinical and paraclinical features, intraoperative findings, and postoperative outcomes were collected using a standardized medical record form and analyzed using medical statistical methods. Results: The age group 31–60 years accounted for the highest proportion (53.0%), with females outnumbering males (42 vs. 24). Most patients were admitted within 24 hours of symptom onset (71.2%). Typical clinical manifestations included right lower quadrant pain (62.1%), continuous pain (90.9%), and nausea/vomiting (77.3%). Intraoperatively, purulent peritoneal fluid was observed in 75.8% of cases; the appendix was located in the right iliac fossa in 77.3%, with suppurative appendicitis accounting for 54.5% and perforation for 19.7%. The antegrade appendectomy technique was predominantly used (92.4%), and the appendiceal stump was mainly managed with clips (89.4%). The mean operative time was 91.41 ± 28.85 minutes, and the conversion rate to open surgery was 6%. Postoperatively, bowel motility most commonly returned on the second day (54.5%), with a low complication rate (9.1%) and no mortality. The length of hospital stay was mainly 5–7 days (68.2%). Early outcomes were favorable in 95.5% of cases, and favorable outcomes at 3 months were observed in 98.2%. Conclusion: Laparoscopic appendectomy for acute appendicitis is a safe and effective method with low complication rates, rapid recovery, and is suitable for implementation at district-level healthcare facilities.